Prevalence, correlates of psychological distress and mental health challenges among college and university students during the COVID-19 lockdowns in South Africa - Sifunda, Sibusiso; Sewpaul, Ronel; Mokhele, Tholang; Mabaso, Musawenkosi; Naidoo, Inbarani; Dukhi, Natisha; Parker, Saahier; Davids, Adlai; Zungu, Nompumelelo; Shisana, Olive; Makgalemane, Ruth; Thakoordeen-Reddy, Semone; et al. (Frontiers in Education, 2024)
IntroductionThe outbreak of the SARS COVID-19 pandemic in late 2019 led to a total disruption of life and impacted mental health negatively worldwide. Studies across many countries showed the impact of COVID-19 on the mental health status of students enrolled in higher institutions due to the disruption of the school year and learning. This study was aimed a measuring the prevalence and psychosocial determinants of psychological distress experienced by college and university students during the COVID-19 lockdowns in South Africa.MethodsStudents aged 18–35 years that were enrolled at tertiary institutions nationally were invited to participate in the online survey. The survey was conducted at the peak of the epidemic in South Africa from 18 June till 18 September 2020. The Kessler −10 (K10) screening scale was used to measure psychological distress among students.ResultsA total of 6,810 young people aged of between 18 and 35 years participated in the study. The majority of these students were aged between 18 and 24 years old (83.9%). About one third (66.7%) of the youth reported that they had mild to severe distress (MSD). The prevalence of psychological distress among the youth differed significantly by age group, gender, risk perception of contracting COVID-19, year of study, institution and community type (p < 0.05). Logistics regression investigated the socio-demographic factors associated with psychological distress. Older students aged 25–29 years (aOR = 0.74, 95% CI 0.62–0.88) and 30–35 years (aOR = 0.73, 95% CI 0.55–0.97), male students (aOR = 0.83, 95% CI 0.72–0.95) and those with moderate (aOR = 0.68, 95% CI 0.49–0.95), low (aOR = 0.41, 95% CI [0.30–0.57]) and very low (aOR = 0.22, 95% CI 0.16–0.31) risk perceptions of contracting COVID-19 were significantly less likely to experience MSD. Fourth year students (aOR = 1.39, 95% CI 1.14–1.69), and students in universities of technology (aOR = 1.56, 95% CI 1.20–2.04) were significantly more likely to have MSD.DiscussionThis study showed high prevalence rates of psychological distress among students during the COVID-19 pandemic. These finding highlights the need for tertiary institutions to put holistic mental health services and interventions at the center of their health and wellness programs.